PERMOHONAN PENDAFTARAN MEREK MELALUI KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DI WILAYAH PROPINSI BALI - Desta Yusa Diantara, Kadek; Sukihana, Ida Ayu; Sandhi Sudarsana, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2015)
The brand is one part of the IPR (Intellectual Property Rights), Which has aprotective law to its rightful owners. Validity of an ownership brand because thebrand owner has registered the brand to gain legal protection to be used for theirintended purpose and to prevent abuse of the registered trademark by anotherparty. Registration of brands held by the Indonesian goverment througt yhe pf lawand human rights in the respective province called decentralized authority.
Keywords: The Brand, Protective Law, Decentralized